2003
DOI: 10.1902/jop.2003.74.7.965
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alveolar Bone Height and Width Following Post‐Extraction Ridge Augmentation Using a Fixed Bioabsorbable Membrane and Demineralized Freeze‐Dried Bone Osteoinductive Graft

Abstract: Results indicate a complete loss of augmented width 3 mm from the crest and almost complete loss in height and width 5 mm from the crest. Membrane stabilization appeared beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 40 publications
2
69
2
2
Order By: Relevance
“…Interestingly, Fugazzotto 33 in a report on a comparison of resorbable and titanium-reinforced membranes used with Bio-Oss found that ''significant bucco-lingual ridge collapse was noted upon re-entry''. The findings of this paper are supported by the work of Zubillaga et al 34 who showed that tacked membranes in place results in less loss of augmented bone than non-tacked membranes.…”
Section: Bone Grafts and Membranes Togethersupporting
confidence: 85%
“…Interestingly, Fugazzotto 33 in a report on a comparison of resorbable and titanium-reinforced membranes used with Bio-Oss found that ''significant bucco-lingual ridge collapse was noted upon re-entry''. The findings of this paper are supported by the work of Zubillaga et al 34 who showed that tacked membranes in place results in less loss of augmented bone than non-tacked membranes.…”
Section: Bone Grafts and Membranes Togethersupporting
confidence: 85%
“…Several studies have reported significant structural changes and bone reabsorption in fresh sockets following tooth extraction, with important dimensional changes in the surrounding alveolar bone (1)(2)(3). A reduction of alveolar bone may present problems after tooth extraction, especially in aged individuals in whom bone volume is important for both physiological and medical reasons.…”
mentioning
confidence: 99%
“…41,42 Sinus lift surgery has been used by the dental profession to increase bone volume in the posterior maxilla and currently, the treatment of choice for posterior dental implant anchorage. [43][44][45][46][47] Density of host bone is crucial for implant [50][51][52][53][54] Guided dental surgery is a concept whereby the planning and installation of an implant is controlled to achieve precise results. [55][56][57][58][59][60][61] A number of guided surgery possibilities exist utilizing either analogue or digital technologies.…”
Section: Introductionmentioning
confidence: 99%